The Influence of Cutting Edge Angles Included Angle and Nose Radius on Surface Finish of Aluminum Alloy 1050 in Turning. - Rzgar M. Abdalrahman; Shawbo A. Hama Sure (Zanco Journal of Pure and Applied Sciences, 2020)
The tool geometry is one of the most effective factors on the surface quality of turned products. This study aims to investigate the influence of different tool geometries on surface roughness of turned aluminum alloy 1050 that has not been documented well in literature. Various levels of simultaneous cutting edge angles, included angle and tool nose radius were selected. Different single point tools of HSS (5% cobalt) were prepared. Four categories of experiments were performed according to the levels of the included angle. Each category consisted of five sets of tests based on the proposed levels of tool nose radius. The tests within each set were arranged according to the selected levels of end cutting edge angle with constant or simultaneous cutting edge angle. All tests were conducted on a heavy duty lathe machine, while the produced surface qualities were measured by a stylus type roughness tester. Experimental results deduced a proportional relationship between surface roughness and end cutting edge angle with constant cutting edge angle. Also, the results showed that the surface roughness increases with the increase of simultaneous end cutting edge angle up to a certain point called focus point angle after which decreases. Furthermore, the tool nose radius has an inverse effect on roughness, but the included angle affects positively. Finally, the maximum values of simultaneous end cutting edge angle that can produce acceptable surface finish were defined in accordance with the tool nose radii and included angles.